DINÁMICAS PERIODÍSTICAS DE LOS MEDIOS DE COMUNICACIÓN RADIOFÓNICOS EN EL ESCENARIO DIGITAL - SORIANO ALARCÓN, MARYLIN MAYERLY (2024)
The present case study is framed in the line of research of the strengthening and innovation of the journalistic dynamics of the radio media in the digital scenario, the current challenges of journalists, the most used dissemination channels and the necessary skills of the journalists. journalists within this field. The methodological design used corresponds to a mixed approach, from an interpretive perspective, it sought to evaluate the digital scenario, the journalistic dynamics of the radio media in the meaning of an experience, it is also heuristic, since it tries to illuminate the understanding of the reader about the social phenomenon under study. It is phenomenological in nature, because, by approaching the field, we can make an analysis of the subjective and objective part of the individuals; on the other hand, it is longitudinal, since the data are collected to construct the information. Within this research, the members of the institution's staff are taken into account as the population, and the data collection instruments are the observation sheets, the survey and the documentary review, in order to analyze the different contexts that comprise the stations N Radio, Radio LIBRE, Radio Fluminense and Radio LIFE, through the results obtained it was possible to develop the respective interpretations which was the starting point to identify the journalistic skills, the most used media and the challenges they face in the journalists in the digital scenario today.